Prevalence and determinants of susceptibility to tobacco smoking among students in the Gambia - Jallow, Isatou K.; Britton, John; Langley, Tessa (Oxford University Press, 2018)
Introduction: Smoking is the biggest preventable cause of death, and kills about 7 million people annually. As smoking prevalence is falling in developed countries, tobacco businesses are turning to low and middle-income countries (LMICs) to generate new tobacco markets. To prevent young people from initiating smoking and becoming regular smokers it is important to understand the causes of susceptibility to smoking. In this study we report a nationwide survey of the prevalence and risk factors of smoking susceptibility among students aged 12-20 in The Gambia.